math

A=1/2h (b1 + b2)

Solve for b1

A=1/2h (b1 + b2)

Solve for b1

I assume this is A = (1/2)(h)(b1 + b2); i.e., the h is in the numerator and not the denominator
Multiply both sides by 2.
2A = (2*1/2)h(b1 + b2).
2*1/2 on the right side is 1.
2A = h(b1 + b2)

expand the right side.
2A = hb1 + hb2.

Subtract hb2 from both sides.
2A - hb2 = hb1 + hb2 - hb2.
The hb2 terms on the right "cancel" or add out.
2A - hb2 = hb1

Divide both sides by h, leaving just b1 on the right side.
[(2A - hb2)/h] = (hb1/h) = b1

I hope this helps. Check my work.

If I divide everything by 2 at the end. Where does the A go.

Would it be Ab2/h = b1

Im kind of lost

Why do you wish to divide everything by 2 from the last step? That will give you 1/2*b1 on the right and you wanted to solve for b1, not 1/2 b1.
Just remember that you can do anything to the equation to get it in the form you wish but whatever you do to one side you must do to the other side. If you are still lost, post what step you don't understand and tell us exactly the problem you are having in taking the next step.

thank you for the help.

is the equation if you were solving for B2
[(2A-hb2)/h]=(hb2/h)=b2 ?????

So what's the answr in the end??

  1. 👍
  2. 👎
  3. 👁
  1. what if i was solving for h? what would i do?

    1. 👍
    2. 👎
  2. A=1/2h(b1+b2) Solve for h

    1. 👍
    2. 👎
  3. Solve for b2: A=1/2h(b1+b2)

    1. 👍
    2. 👎

Respond to this Question

First Name

Your Response

Similar Questions

  1. How do I do this.?(Math.)

    Use the Substitution method to solve the system of equations. y - 2x = -5 3y - x = 5 Solve one of the equations for x or y. Let's solve the first one for y: y - 2x = -5 y = 2x - 5 Now let's substitute 2x - 5 for y in the second

  2. Physics

    When you see a traffic light turn red, you apply the brakes until you come to a stop. Suppose your initial speed was 12.9 m/s, and you come to rest in 35.0 m. How much time does this take? Assume constant deceleration. What

  3. Math check please

    1. Solve the system of equations y=2x^2-3 y=3x-1 a)no solution b)(-1/2,5),(2,-5/2) c)(-1/2,-5/2),(2,5)**** d)(1/2,5/2),(2,5) 2. How many real number solutions are there to the equation 0=-3x^2+x-4? a)0 ***** b)1 c)2 d)3 3.solve

  4. math

    What is the first step in solving the linear system {2x − 3y = 11 {−x + 5y = −9 by the substitution method in the most efficient way? A. Solve the first equation for x. B. Solve the first equation for y. C. Solve the second

  1. Math help please

    1. Solve for x. 4(x - b) = x b = 4/3x b = 3/4x x = 4/3b x = 3/4b 2. Solve for y, then find the value of y when given x = 2. 6x = 7 - 4y -12 7/4 19/4 24 I need help solving these. Can you please explain how to solve these problems?

  2. Algebra

    To solve the system of equations, which expression could be substituted for x into the first equation? 3x-5y=14 x+4y=10 a)10-4y b)4y+10 c)(1/4)x+(5/2) d)(-1/4)x+(5/2) I have another problem just like this one so if you could

  3. math

    What is the first step in solving the linear system {2x−3y=11 {−x+5y=−9 by the substitution method in the most efficient way? A. Solve the first equation for x. B. Solve the first equation for y. C. Solve the second equation

  4. economics

    Assume that the equation for demand for bread at a small bakery is Qd = 60 - 10Pb + 3Y, where Qd is the quantity of bread demanded in loaves, Pb is the price of bread in dollars per loaf, and Y is the average income in the town in

  1. Physics

    Can someone help me solve this problem? This example problem will help me solve the actual homework problems If an 0.6kg apple is dropped from 0.5m height onto a seesaw and flips up a 0.25kg kiwi. To what height does that kiwi

  2. algebra

    solve for the indicated variable: a. temperature formula solve for F: K=5/9(F-32)+273 b. annual interest rate solve for R: A=P+Prt

  3. algebra

    1. solve 2x + y = 7 for y 2. solve 2y - 18x = 26 for y 3. solve 20x + 5y =15 for y 4. solve 9x - y = 45 for y 5. solve 6x - 3y = -6 for y 6. solve 4x - 5 = 7 + 4y for y

  4. Substitution Method-Plz help

    Use the Substitution method to solve the system of equations. x + y = -4 x - y = 2 solve for x in the second equation. x= y+2 Put that in for x in the first equation: x+y=-4 (y+2) + y = -4 solve for y. Then, x= y+2 i don't get

You can view more similar questions or ask a new question.